DEFAULT WITH FRAUD IN A DEBT AGREEMENT - Hari Panri Nst; Tri Reni Novita (Fox Justi : Jurnal Ilmu Hukum, 2022)
This research is about Analysis of Default with Fraud in Debt Agreements in Deli Serdang Regency, Medan City. Problem Formulation How is the difference between default and fraud in a debt agreement? What are the obstacles faced in resolving cases of default with fraud in the debt agreement? What efforts are made in resolving cases of default with fraud in the debt agreement? The purpose of this study is to determine the difference between default and fraud in accounts payable agreements. To find out what obstacles are faced in resolving cases of default with fraud in the debt agreement. To find out what efforts are being made in resolving cases of default with fraud in accounts payable agreements. The type of research used is normative and empirical legal research. The results of the study of the difference between default and fraud in accounts payable agreements are that the debtor continues to perform but is only able to pay off part of his debt to the debtor and cannot pay off all his debts to the debtor. In this case, there were several obstacles that occurred the contents of the plaintiff's special power of attorney were incomplete. In this case Defendant 1 could not complete the construction because the building permit was not issued for the land contained in the Certificate of Ownership no. 520 By the Department of Settlement and Spatial Planning Medan City. And in this case also Defendant II could not submit the Certificate of Ownership No. 520 to the plaintiff due to the absence of consent from the defendant I. The legal settlement in the case of default on the debt agreement carried out by Zulkarnai against Mr. Salim and Mrs. Devi Juliastuti was pursued through the courts. Mr. Salim and Mrs. Devi Juliastuti as defendants never attended the trial even though he had been legally and properly summoned, so the judge decided to impose a versteeek verdict on this case.